The feeding ecology and habitat use of the aardvark (Orycteropus afer) - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases)--University of Pretoria, 1999.